Holistic interventions for autism: a Malaysia–Indonesia multidisciplinary collaboration - Idris, Sakinah (Faculty of Medicine, 2026)
The Webinar on Holistic Interventions for Autism Through Multidisciplinary Lens was successfully conducted as part of the official academic activities under the Memorandum of Understanding (MoU) between Universiti Teknologi MARA (UiTM), Malaysia and Paramadina University, Indonesia. This webinar is a collaborative effort between Department of Psychiatry, and Department of Rehabilitation Medicine, Faculty of Medicine, UiTM, School of Psychology, Faculty of Philosophy and Civilization, Paramadina University, and IDEAS Autism Centre Malaysia, a centre that provides the intervention for children with autism spectrum disorder (ASD).